Correlation power analysis and effective defense approach on light encryption device block cipher. Issue 5 (13th August 2019) - Rai, Vikash Kumar; Reddy, Boreddy V.; Tripathy, Somanath; Mathew, Jimson
Abstract: Recently many works have shown that one of the weaknesses of cryptographic algorithms is power analysis attacks on its hardware implementation. This side channel analysis (SCA) is of interest because such attack can leak information of cryptographic algorithms. So, developing attack resistant mechanism is important for hardware security modules. This paper investigates the vulnerability of light encryption device (LED) block cipher, against correlation power analysis. LED is a lightweight block cipher targeted for compact hardware implementation to protect ubiquitous computing data. We use Chipwhisperer capture hardware to capture power traces during encryption of randomly generated plain texts using the same secret key. Our proposed attack successfully retrieves all 64 bits of secret key correctly using only 300 power traces and 256 key guesses. Furthermore, we propose a simple but effective mitigation technique to prevent such attacks.